Lessons from Innovation Economics for Digital Platform Policy - Johannes M. Bauer; Tiago S. Prado (International Telecommunications Society (ITS), 2020)
This paper relates to current concerns about the high concentration of digital platform markets and the effects of large companies such as Amazon, Facebook, Google, and Microsoft, on innovation. Several stakeholders and analysts assert that digital platforms have become so dominant that they slow the speed of innovation and that regulatory and antitrust intervention is needed to protect the public interest. Despite the strong claims, few systematic studies have examined the positive and negative effects of digital platforms on innovation. This paper seeks to contribute to closing this gap by pursuing three overarching objectives. First, it develops a theoretical framework to deepen our understanding of the multi-faceted relations between digital platforms and innovation. Second, it discusses which empirical evidence could be used to examine the multitude of potential, positive and negative, impacts. Third, the paper discusses the implications of these largely conceptual arguments for the design of policies toward digital platforms. In contrast to traditional regulatory theory and practice, which often uses static economic optimization models, much of innovation economics emphasizes that incentives to introduce new processes, create new products, services, designs, and business models are strongest in out-of-equilibrium processes. However, there are conditions under which market power and the interests of large companies do not align well with the broader goals of vibrant innovation. The paper argues that the most promising instruments to address these issues affect the constitution of digital markets.
Keywords: L86; L96; 330; Digital platforms; innovation economics; innovation ecosystems; market power; regulation; competition policy